2022
DOI: 10.3892/mmr.2022.12634
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis‑related long non‑coding RNAs and the roles of LASTR in stomach adenocarcinoma

Abstract: Ferroptosis is a form of programmed cell death that participates in diverse physiological processes. increasing evidence suggests that long noncoding rnas (lncrnas) regulate ferroptosis in tumors, including stomach adenocarcinoma (STad). in the present study, rna-sequencing data from The cancer Genome atlas database and ferroptosis-related markers from the Ferrdb data resource were analyzed to select differentially expressed lncrnas. univariate and multivariate cox regression analyses were performed on these d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…However, no study has reported a direct correlation between LASTR and immunity. Interestingly, LASTR has also been used as a ferroptosis-related marker in stomach adenocarcinoma [ 32 ]. Therefore, there are some connections between cuproptosis and ferroptosis, and LASTR could be involved in the cross-talk between them, thus playing an essential role in the immunological therapy of cuproptosis and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study has reported a direct correlation between LASTR and immunity. Interestingly, LASTR has also been used as a ferroptosis-related marker in stomach adenocarcinoma [ 32 ]. Therefore, there are some connections between cuproptosis and ferroptosis, and LASTR could be involved in the cross-talk between them, thus playing an essential role in the immunological therapy of cuproptosis and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…U62317.1 acts as a risk factor in oral cancer and tends to be associated with the lipid metabolic process [ 32 ]. LASTR has been proved to promote the stomach adenocarcinoma growth and lung cancer [ 33 , 34 ]. LINC01126 could repress proliferation, increase apoptosis, and cause inflammatory of hPDLCs in anaerobic environment via sponging miR-518a-5p to promote periodontitis pathogenesis in humans [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the lncBDNF-AS/WDR5/FBXW7 axis regulated ferroptosis and mediated peritoneal metastasis of GC through VDAC3 ubiquitination ( Huang et al, 2022 ). The experiment of Wang et al confirmed that lncLASTR mediated the proliferation and migration of GC cells through the regulation of ferroptosis ( Wang G. et al, 2022 ). GC stem cells (GCSC) are the main cause of the occurrence and prognosis of GC.…”
Section: Ferroptosis-related Non-coding Rna and Gastric Cancermentioning
confidence: 94%